1993
DOI: 10.1128/aac.37.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone resistance protein NorA of Staphylococcus aureus is a multidrug efflux transporter

Abstract: The gene of the Staphylococcus aureus fluoroquinolone efflux transporter protein NorA confers resistance to a number of structurally dissimilar drugs, not just to fluoroquinolones, when it is expressed in Bacillus subtilis. NorA provides B. subtilis with resistance to the same drugs and to a similar extent as the B. subtilis multidrug transporter protein Bmr does. NorA and Bmr share 44% sequence similarity. Both the NorA- and Bmr-conferred resistances can be completely reversed by reserpine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
227
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(232 citation statements)
references
References 6 publications
3
227
0
2
Order By: Relevance
“…aureus is provided by the membrane protein NorA encoded in the bacterial chromosome (12,15). Also, over-expression of…”
Section: Fluoroquinolone Resistance Of Several Clinical Isolates Of Smentioning
confidence: 99%
“…aureus is provided by the membrane protein NorA encoded in the bacterial chromosome (12,15). Also, over-expression of…”
Section: Fluoroquinolone Resistance Of Several Clinical Isolates Of Smentioning
confidence: 99%
“…For example, human P-glycoprotein, the product of the MDR1 gene, is highly homologous to the protein MDR2, which does not efflux drugs but is a specific phosphatidylcholine flippase (6). Similarly, the bacterial multidrug transporters Bmr and Blt of Bacillus subtilis and NorA of Staphylococcus aureus are highly homologous to the efflux transporters whose only known substrate is tetracycline (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…an increase in MIC, has been attributed mainly to the excretion of drugs into the extracellular space by proton motive forcedependent multidrug-transport systems (Grinius et al, 1992;Kaatz et al, 1993;. In S. aureus, qacA (Rouch et al, 1990), qacB (Paulsen et al, 1996), smr (Grinius et al, 1992) and norA (Neyfakh et al, 1993), which encode multidrug-transporter proteins, have been identified as antiseptic-resistance genes which confer resistance to cationic antiseptic agents including dyes such as acriflavine, acrinol and ethidium bromide, quaternary ammonium compounds (QACs) such as benzethonium chloride and benzalkonium chloride, and biguanides such as chlorhexidine digluconate (Littlejohn et al, 1992;. Therefore, an MRSA strain with decreased suscept-ibility to antiseptic agents mediated by an antiseptic-resistance gene is interpreted as an antiseptic-resistant strain (Lyon & Skurry, 1987).…”
Section: Introductionmentioning
confidence: 99%